Depression Level Among Neurology Resident Doctors in the Faculty of Medicine, Universitas Indonesia - Dyah Perwitasari, Vina; Hidayat, Rakhmad (Acta Neurologica Indonesia, 2024)
Introduction: A resident doctor is a doctor who has graduated from medical school, has earned the title of "doctor" and is currently undergoing a specific specialization postgraduate program. Resident doctors are at high risk of experiencing stress and depression. Depression greatly affects the quality of medical services provided by residents. Objective: This study aimed to determine the prevalence of depression, its relationship with various sociodemographic factors and several environmental factors, and its relation to the residency level of resident doctors in the Neurology Study Program, Faculty of Medicine, Universitas Indonesia. Material and Methods: This research was an analytic observational study with a cross-sectional design. All neurology resident doctors of Universitas Indonesia had filling out a questionnaire containing sociodemographic data and the Beck Depression Inventory-II (BDI-II) via Google Form platform. Then, the data were analyzed using chi-square and regression analysis. Result: In this study, 53 (66.2%) participants were females and 16 (33.8%) were males. Sixty-five participants were analyzed with 4 participants excluded. The overall prevalence of depression was 18.2%, with mild depression at 9.2% and moderate depression at 9.2%. Depression was more common in females than males (10.8% vs 7.7%). The residency level and supervisor support have a significant association with the incidence of depression. Conclusion: Our study found that 18.4% of neurology resident doctors had depression. Residency level and senior/supervisor support were significantly associated with depression among resident doctors.